2010
DOI: 10.1148/radiol.10091487
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Lung Disease: CT of the Chest with Adaptive Statistical Iterative Reconstruction Technique

Abstract: ASIR-HD reconstruction results in superior visualization of subtle and tiny anatomic structures and lesions in diffuse lung disease compared with ASIR and filtered back projection reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(87 citation statements)
references
References 15 publications
5
80
0
2
Order By: Relevance
“…While each elementary lesion was identified on the 3 series of images, the visual depiction of ground glass opacities, ill-defined micronodules and emphysematous lesions was improved on Group 2a compared with reference images. Further comparison between the two levels of iterative reconstructions showed greater conspicuity of ground glass opacities and emphysematous lesions on Group 2b images, confirming that reduction of the objective image noise reinforces the detectability of subtle abnormalities, as also recently reported by Prakash et al with the ASIR technique [18]. Although depiction of illdefined micronodules can also be influenced by the overall image quality, their conspicuity was not found to be increased on Group 2b images, probably because of the limited number of images showing this pattern.…”
Section: Discussionsupporting
confidence: 84%
“…While each elementary lesion was identified on the 3 series of images, the visual depiction of ground glass opacities, ill-defined micronodules and emphysematous lesions was improved on Group 2a compared with reference images. Further comparison between the two levels of iterative reconstructions showed greater conspicuity of ground glass opacities and emphysematous lesions on Group 2b images, confirming that reduction of the objective image noise reinforces the detectability of subtle abnormalities, as also recently reported by Prakash et al with the ASIR technique [18]. Although depiction of illdefined micronodules can also be influenced by the overall image quality, their conspicuity was not found to be increased on Group 2b images, probably because of the limited number of images showing this pattern.…”
Section: Discussionsupporting
confidence: 84%
“…Noise and artifact reductions are necessary steps toward dose reduction in CT. The recent burst of research activities in iterative reconstruction can also be credited to the increased awareness of the radiation dose generated by a CT scan [52][53][54][55][56][57][58][59], and advancements in reconstruction hardware capability.…”
Section: Iterative Reconstructionmentioning
confidence: 99%
“…Vorona et al (5) reported a 37% dose reduction at 40% ASIR with acceptable image quality for a pediatric abdominal CT. Another study (6) at low X‐ray tube voltage and high X‐ray tube current showed that noise was significantly reduced using low‐dose ASIR and that the CNR was improved for some anatomical organs (the aorta and pancreas) but remained unchanged for other organs (the liver). Chest diagnosis using ASIR and ASIR‐high definition (ASIR‐HD) has shown acceptable image quality or improved confidence 7 , 8 , 9 . Hara et al (10) reported that using ASIR with a 50% lower radiation dose compared to the routine dose can still fulfill the American College of Radiology (ACR) criteria in terms of low and high contrast; (11) however, the high‐contrast resolution is better when using the standard dose.…”
Section: Introductionmentioning
confidence: 99%